Practical Labeling Methodology for Choline‐Derived Lipids and Applications in Live Cell Fluorescence Imaging. (31st January 2014) - Li, Caishun; Key, Jessie A.; Jia, Feng; Dandapat, Arpan; Hur, Soo; Cairo, Christopher W.
Abstract Lipids of the plasma membrane participate in a variety of biological processes, and methods to probe their function and cellular location are essential to understanding biochemical mechanisms. Previous reports have established that phosphocholine‐containing lipids can be labeled by alkyne groups through metabolic incorporation. Herein, we have tested alkyne, azide and ketone‐containing derivatives of choline as metabolic labels of choline‐containing lipids in cells. We also show that 17‐octadecynoic acid can be used as a complementary metabolic label for lipid acyl chains. We provide methods for the synthesis of cyanine‐based dyes that are reactive with alkyne, azide and ketone metabolic labels. Using an improved method for fluorophore conjugation to azide or alkyne‐modified lipids by Cu(I)‐catalyzed azide‐alkyne cycloaddition (CuAAC), we apply this methodology in cells. Lipid‐labeled cell membranes were then interrogated using flow cytometry and fluorescence microscopy. Furthermore, we explored the utility of this labeling strategy for use in live cell experiments. We demonstrate measurements of lipid dynamics (lateral mobility) by fluorescence photobleaching recovery (FPR). In addition, we show that adhesion of cells to specific surfaces can be accomplished by chemically linking membrane lipids to a functionalized surface. The strategies described provide robust methods for introducing bioorthogonal labels into native lipids.